Management of Prosthesis-patient Mismatch After Aortic Valve Replacement - Demirsoy, Ergun; Demir, İbrahim; Uğur, Murat (Kardiyovasküler tıp e dergisi, 2019)
Valve prostheses have played an important role in the past four decades in the management of patients with valvular heart disease. Many of the devices have been used for valve replacement and they have introduced new clinical problems. One of these problems is prosthesis-patient mismatch (PPM) which is associated with increased mid- and long-term mortality after surgical aortic valve replacement (AVR) and transcatheter aortic valve implantation. The aim of this study was to systematically review the literature on the importance, prevention and feasibility of PPM in AVR and percutaneous-AVR. The articles about PPM published between 2003-2018 were analyzed. The results of surgical and transcatheter methods were discussed together to prevent PPM.